2022
DOI: 10.1155/2022/8422339
|View full text |Cite
|
Sign up to set email alerts
|

Cell Differentiation Trajectory Predicts Prognosis and Immunotherapeutic Response in Clear Cell Renal Cell Carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is the main type of malignancy in kidney related to glucose metabolism. Primary single cell culture and single cell sequencing are novel research technologies. In this study, we explored the differentiation status of ccRCC cells and its significance in prognosis and immunotherapeutic response through bioinformatics. We characterized distinct differentiation states and differentiation-related genes (DRGs) in ccRCC cells through single cell RNA sequencing (scRNA-seq) analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…In the theatre of apoptosis, bid takes center stage, with its malfunction forming the underpinning for oncogenic development and emerging as a credible risk factor in the annals of ccRCC 37 . A previous study found that the emergence of cdkn1a 's antisense DNA damage‐activated RNA promoter as a conspicuous presence in tumour tissues renders it a key protagonist, additionally serving as an independent harbinger of OS in ccRCC 38 . The immunoregulatory gene cx3cl1 emerges as a prominent constituent in the inflammatory milieu of ccRCC, bestowing a pathway to personalized treatment strategies 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the theatre of apoptosis, bid takes center stage, with its malfunction forming the underpinning for oncogenic development and emerging as a credible risk factor in the annals of ccRCC 37 . A previous study found that the emergence of cdkn1a 's antisense DNA damage‐activated RNA promoter as a conspicuous presence in tumour tissues renders it a key protagonist, additionally serving as an independent harbinger of OS in ccRCC 38 . The immunoregulatory gene cx3cl1 emerges as a prominent constituent in the inflammatory milieu of ccRCC, bestowing a pathway to personalized treatment strategies 39 .…”
Section: Discussionmentioning
confidence: 99%
“… 37 A previous study found that the emergence of cdkn1a 's antisense DNA damage‐activated RNA promoter as a conspicuous presence in tumour tissues renders it a key protagonist, additionally serving as an independent harbinger of OS in ccRCC. 38 The immunoregulatory gene cx3cl1 emerges as a prominent constituent in the inflammatory milieu of ccRCC, bestowing a pathway to personalized treatment strategies. 39 ddias , when overexpressed in NCI‐H1299 or NCI‐H1703 cells, assumes an inhibitory role, counteracting the proliferation induced by CHIP overexpression.…”
Section: Discussionmentioning
confidence: 99%